Silicone band loop myopexy in the treatment of myopic strabismus fixus: surgical outcome of a novel modification. Issue 1 (4th August 2014) - Shenoy, Bhamy Hariprasad; Sachdeva, Virender; Kekunnaya, Ramesh
Abstract : Aim: To evaluate safety profile and surgical outcomes of a novel modification of loop myopexy with silicone band for myopic strabismus fixus (MSF). Design: Retrospective interventional case series. Methods: A retrospective chart review of patients who underwent silicone band loop myopexy between January 2008 and December 2012 for MSF at a tertiary eye care centre was undertaken. A minimum of 2 months of follow-up after surgery was required for inclusion. Patients who underwent conventional suture loop myopexy and cases with incomplete details pertaining to the preoperative alignment and movement restriction were excluded. The main outcome measures were improvement in alignment postoperatively, improvement in extra-ocular motility postoperatively, and intraoperative and postoperative complications. Results: 26 eyes of 15 patients (male (9):female (6)=1.5:1) underwent silicone band loop myopexy at a mean age of 27.8±16.4 years (range 7–72 years). Mean follow-up was 7.9±8.4 months (range 2–28 months, and median 4 months). 11 patients underwent bilateral loop myopexy whereas four patients underwent unilateral loop myopexy. 16 eyes underwent additional medial rectus (MR) recession. At the last follow-up, mean abduction limitation improved to −1.5±1.3 from −2.9±1.2, p=0.0000; mean elevation limitation improved to −1.2±0.9 from −2.8±1.1, p=0.0000; mean esotropia improved to 16.9±17.4 prism dioptres (PD) from 79.3±32.3PD, p=0.0000; and success (deviation ≤20PD) was achieved in 73% (95% CI 48 to 89%). Mean hypotropia at presentation was 8.9±10.1PD (range 0–25PD), which improved to 0.6±1.3PD (range 0–4PD), p=0.007. Conclusions: Modified scleral fixated silicone band loop myopexy with or without MR recession is a safe and effective procedure in the management of MSF and improves alignment significantly.